Nanofiber network with adjustable nanostructure controlled by PVP content for an excellent microwave absorption - Lv, Jing (Sci Rep, 2019)
Carbon nanofibers were widely utilized to improve microwave absorption properties since they are a promising lightweight candidate. Adjustable conductive nanostructures of carbon nanofibers were synthesized by electrospinning technique. The conductive network is controlled by the polyvinyl pyrrolidone (PVP) content due to the special hygroscopicity of PVP. The increased adhesive contacts of nanofibers provide more transmission paths for electrons to reduce the effect of air dielectric. Satisfactorily, the carbon nanofibers that carbonized from the polyacrylonitrile (PAN) and PVP (the mass ratio is 6:4) show excellent microwave absorption performance. The minimum reflection loss (RL) value is −51.3 dB at 15.2 GHz and the maximum effective absorption frequency width (<−10 dB) is 5.1 GHz with the matching thickness of only 1.8 mm. Thereby, we believe that this research may offer an effective way to synthesize lightweight carbon nanofibers microwave absorbents.